Corruption in the Americas - Rosen, Jonathan D.; Kassab, Hanna Samir (Lexington Books, 2020)
Introduction / Jonathan D. Rosen and Hanna S. Kassab -- A little lower than the angels : problems of corruption and obligation : a conceptual review / Bradford R. McGuinn -- Corruption, violence, and state fragility in Mexico : an examination of the recent challenges and opportunities / Roberto Zepeda and Jonathan D. Rosen -- Guatemala, a captured state / Adriana Beltrán -- Corruption in Colombia / Fernando Cepeda Ulloa -- Corruption in Peru in the twenty-first century : a tsunami of scandals, a tsunami of prosecution / Cynthia McClintock -- "The police are involved in everything" : corruption and the corrupt in Bolivia / Marten Brienen -- Organized crime and the state in Brazil / Michael Jerome Wolff.